Effect of irrigation levels on the production of Arachis hypogeaea L - Bonfim-Silva, Tallys Henrique; Koetz, Márcio; Bonfim-Silva, Edna Maria; da Silva, Tonny José Araújo; Meneghetti, Luana Aparecida Menegaz; Duarte, Thiago Franco; Guimarães, Salomão Lima (Australian journal of crop science, 2024)
Peanuts (Arachis hypogaea L.) are a high-protein alternative for making up for nutritional deficiencies. Adequate irrigation management is essential for greater productivity of this crop, especially in Brazilian Cerrado. In this context, this study aimed to evaluate the productive characteristics of peanuts subjected to different irrigation levels under controlled conditions. The research was conducted in the Savannah region at the Federal University of Rondonópolis, in Rondonópolis - Mato Grosso, Brazil. The soil used to grow the peanuts was Oxisol. The experimental design was completely randomized with five treatments (50%, 75%, 100%, 125%, and submerging at 150% of field capacity) and five replications. The analyzed variables included the number of pods, number of grains per pod, pod dry mass, and dry mass of grains. The number of pods and the number of grains per pot fitted the increasing linear model as a function of different levels of field capacity. On the other hand, the pod dry mass and dry mass of grains per pod showed a quadratic regression behavior. Different levels of field capacity had a significant impact on peanut productivity. The treatment with 100% of field capacity yielded the best results in terms of peanut productivity and grain quality.